Autonomous Landing Design of UAVs using Feedback Linearization Controller with Anti Windup Scheme. (2020) - Tripathi, Amit Kumar; Patel, Vijay V; Padhi, Radhakant
Abstract: This paper presents autonomous landing controller design of unmanned aerial vehicles (UAVs). Feedback linearization approach with anti windup scheme is designed as autonomous landing controller. Anti windup basically controls the integrator component accumulation in the autopilot design and restricts the output within saturation limits. Autonomous landing of a fixed wing UAV consists of approach, glideslope and flare phases. During approach, aerial vehicle aligns itself with runway and reduces its lateral deviations with respect to runway central line. In glide slope phase, aerial vehicle maintains a fixed flight path angle and descends with a constant sink rate. In flare phase, aerial vehicle follows an exponential trajectory and descends with a lower sink rate which keeps reducing further as it goes to lower altitudes. Flare controller is designed with integrator and antiwindup scheme is used to handle the controller output within saturation limits. Landing is primarily a longitudinal mode operation but due to disturbances and coupling lateral and directional modes also gets activated. In this paper pitch angle, roll angle and yaw angle nonlinear dynamic equations are linearized to obtain the control commands in terms of elevator deflection, aileron deflection and rudder deflections. Similarly total velocity of aerial vehicle being an important parameter is controlled using thrust command. A first order linearized model of velocity is used to obtain thrust control command. Autonomous landing of UAV with feedback linearization controller and anti windup scheme is simulated with Six-DOF model of AE2 UAV. The algorithm is implemented with wind disturbances to show the autonomous landing performance of UAV.